Розвиток ландшафтних театрів України в майбутньому - Проскуряков, В. І.; Гуменник, І. В.; Proskuriakov, V.; Gumennyk, I. (Видавництво Львівської політехніки, 2018)
Окреслено розвиток у майбутньому архітектури ландшафтних театрів сучасної України і визначено тенденції та напрями форм створення театрів на відкритому просторі в різноманітнихз онахкл іматичнихр айонів країни.

The article highlights the ways of landscape theaters architecture development in the future in the modern Ukraine and defines trends and directions of the theater creation forms in open space in various zones of the country’s climatic regions. According to the results of the assistant at the Department of Architectural Environment Design, M. Arch. I. V. Gumennyk under the leadership of Sc. D., Prof. V. I. Proskuryakov, research on the genesis of landscape theaters in Ukraine, we can make the following conclusions: a) theatrical structures in the open space, located in different regions of Ukraine, have their own structured architectural typology; b) the architecture of landscape theaters makes it possible to apply the principles that allow the creation of a multifunctional cultural entertainment facility in the real outdoor landscape. As a result of the researches, the authors claim that the environment, urban or historical landscape space acts as an obligatory component of the theatrical structure, which harmoniously combines into one whole nature, the architecture of buildings and stage-viewer space of the created object. As of today, the following vectors for the landscape theaters architecture formation in Ukraine in the future can be foreseen: 1) outdoor theaters with a complete set of electronic equipment for lighting, sound recording and scenography of the landscape theater architectural environment; 2) open-air theatrical structures with a small amount of used technical equipment and innovative technologies that ensure the chamber perception of a cultural event; 3) landscape theaters of a budget type, which are formed on the basis of national cultural and historical traditions with limited use of the latest technical devices and special effects. Prospects for the landscape theaters creation in Ukraine in the XXI century should be considered promising as the historical preconditions laid the foundation for expanding the number of new and reconstruction of existing cultural-spectacular objects in the open space. All theatrical structures, which are located in a landscape environment in the open space, which include objects of anthropogenic and natural origin, act as integral parts of a holistic open air theatrical-entertainment and leisure establishment throughout the territory of Ukraine.
Development of landscape theaters of Ukraine in the future
Keywords: ландшафтний театр; глядацький зал; сцена; відкритий простір; об’ємно-просторове середовище; мультимедійні технічні засоби; інноваційні технології; landscape theater; auditorium; scene; open space; space-spatial environment; multimedia technical devices; innovative technologies; 725.822.5